Effects of Dry Figs on Primary Dysmenorrhea Symptoms, perceived Stress Levels and the Quality of Life - Amanak, Keziban (Puerto Rico Health Sciences Journal, 2020)
Objective: The aim of this study was to examine the effects of eating dried figs on the symptoms of primary dysmenorrhea, perceived stress levels, and quality of life during all menstrual cycles. Methods: This randomized, placebo-controlled study was performed with 115 midwifery students. Each student was randomly assigned to the placebo (n = 31), cinnamon (n = 33), or dried fig (n = 34) groups. Data were gathered through the Total Dysmenorrhea Score, a descriptive information form, the Visual Analogue Scale, a pain duration assessment form, the Menstrual Distress Questionnaire, the Perceived Stress Scale, and the short version of the World Health Organization Quality of Life Scale-TR. Results: During the 3 menstrual cycles in which the intervention was implemented, the dried-fig group had significantly lower scores for pain severity and duration, menstrual distress, and perceived stress than did those of the cinnamon and placebo groups. In addition, during these 3 cycles, the dried-fig group had significantly higher quality-of-life scores than the cinnamon and placebo groups. Conclusion: The results showed that eating dried figs during menstruation decreased pain severity and duration, menstrual symptoms, and perceived stress and increased quality of life.